Spontaneous haemorrhagic stroke associated with expanded dengue syndrome: a case report - Mayung, Claraiva; Thiodorus, Fira; Yuliani, Desie; Sumada, I. Ketut; Jayanti, Kurnia Dwi (International Journal of Advances in Medicine, 2023)
The term "expanded dengue syndrome" was introduced to describe the severe clinical manifestations that result from dengue fever (DF), namely severe multi-organ involvement including disorders of the nervous system. Neurological complications occur in 1-5% of dengue patients, including haemorrhagic stroke. A 68-year-old man presented with complaints of full-body convulsions for 1 minute. Four days earlier the patient complained of headache, fever, and nausea. Non-contrast CT scan of the head showed abnormal hyperdense lesions with focal intraparenchymal oedema in the frontoparietoocipital region, cortical sulci and gyri appeared dilated, ventricular system and sisterna were dilated. Anti-dengue IgG and IgM were positive. Neuropathogenesis that may play an important role in dengue-related neurological syndromes include direct CNS invasion by the virus, autoimmune reactions, and metabolic changes. The diagnosis of neurological complications related to dengue haemorrhagic fever (DHF) requires special attention, especially for areas where DF is still endemic.